Sustainability of Open Education Through Collaboration - de Langen, Frank (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
The definition of openness influenced the sustainability of business models of Open Education (OE). Yet, whether openness is defined as the free (re)usage of resources, or the free entry in courses, there always is a discussion on who pays for the resources used in these offerings. The free offering of courses or materials raises the question if OE can be maintained independent of large government subsidies. This article analyzes four cases that each have a different approach to OE and (financial) survival. The aim of this study is to determine the most efficient conditions for a sustainable OE business model. Instead of using different earning models, this research concentrates on the different aspects of unbundling (costs, income, and financiers), arguing that an adjusted Business Model Canvas can be used to analyze the not-for-profit organizations in higher education institutions (HEIs). The cases are OpenupEd, FemTechNet, MERLOT, and Lumen Learning. Openness plays different roles in the business models of the different organizations. For OpenupEd and MERLOT, openness of the materials offered to students and teachers (MOOCs, OER) is essential. For FemTechNet, openness is part of the need to collaborate and share within their community. Commercial organizations, such as Lumen Learning, use free materials to teach educational organizations to use these materials for their own courses. All four organizations use different key activities and key resources (for example, management competencies, social skills, or design and teaching skills) for their continuity. Yet, despite the differences between the case-organizations, community building is important in all cases. Either because producers and users of Open Education become identical, because standardization does decrease costs and increases findability and quality, or because they can bridge the difference between supply and competences necessary for usage of Open Education.